Pariwisata di Tengah Pandemi: Studi Kasus Tentang Pola Wisata Alternatif di Malang, Jawa Timur - Hipolitus Kristoforus Kewuel; Nindyo Budi Kumoro; Mayang Anggrian (Universitas Negeri Medan, 2022)
Even when the tourism industry in Indonesia has been devastated due to COVID-19 pandemic, this sector has not simply disappeared and succumbed. Some tourist destinations are still visited by tourists from big cities of Indonesia, although the numbers are not as much as before. Malang is a representative place to watch this phenomenon, there are certain moments where tourists still visit and have recreation there. This research questions what is the new or alternative pattern for people who continue to travel in the midst of a pandemic? This is interesting because previously the known tourism pattern was mass tourism (full of crowds and high mobility) which was difficult to do in the pandemic era. This research aims to identify the alternative (niche tourism) specifically its new patterns in the pandemic era in Malang, related to the form of attraction to the socio-demographic character of the tourist. In addition, it is also important to study how tourists view COVID-19 which allows them to travel. With the ethnographic method, this research seeks to find the appropriate new pattern for tourism development in Indonesia during a pandemic.